EFEK MANGROVE TERHADAP PEREDAMAN ENERGI GELOMBANG - Riska Yanti; Pou Anda; Muliddin Muliddin (Jurnal Rekayasa Geofisika Indonesia, 2022)
The research was conducted in Malalanda Village and Linsowu Village, North Buton Regency in November 2021 by collecting primary data (interviews and direct measurements in the field) and processing secondary data to determine the role of mangroves in reducing wave energy based on mangrove conditions (density, thickness and diameter of mangrove trunks). ) using the Thaha Method (2001). Wave conditions in the Kulisusu Bay area are predicted using wind data from the Beto Ambari Bau-Bau BMKG Station followed by predictions of the height and depth of the breaking waves. Changes in shoreline at two research stations that have different coastal protection (dykes and mangrove forests) were analyzed using ArcGIS 10.3 software and then expressed changes in shoreline in quantitative units. Based on the results of the analysis, it was found that the maximum wave height in the study area ranged from 2.27 m – 3.9 m with a maximum breaking wave height of 2.50 m and 3.57 m at a depth of 1.07 m – 3.15 m at a distance of 100 m to 200 m. The change in shoreline is greater at station 2, which is 6.48 m, and the condition of the mangrove forest at the research station has a thickness of 65.61 m and a porosity of 0.72 capable of damping waves with values ranging from 26.424% - 99.98%.Keywords: wave, mangrove, wave attenuation